Laplace Transform: Developing the Variational Iteration Method - JHANSI LAKSHMI, M. (International Journal of Psychosocial Rehabilitation, 2021)
The classification of the Lagrange multiplier plays an import rule in the variational method, and the variational theory is widely used for this purpose. This paper suggests an easier approach by the Laplace transform to determining the multiplier, making the process accessible to researchers facing different nonlinear problems. A nonlinear oscillator is adopted as an illustration to elucidate the detection process and the solution process; only one iteration leads to an ultimate result.